FAKTOR-FAKTOR YANG BERKORELASI DENGAN DUKUNGAN KELUARGA TERHADAP PENDERITA DIABETES MELITUS TIPE 2 SELAMA PANDEMI DI KELURAHAN PONDOK PETIR TAHUN 2021 - Sinta Pratiwi Burhanudin, (2022)
COVID-19 pandemic has caused Posbindu PTM to be temporarily closed in order to minimize the transmission of diseases so it impacted on the behavior of health checks in Type 2 Diabetes Mellitus (DM) patients. This study aims to identify correlated factors with family support towards Type 2 DM patients by using quantitative methods, cross sectional study and purposive sampling techniques. Total samples in this study were 230. Based on the Spearman analysis, the results show positive correlation between work (p-value = 0.001) with family support and have weak close relationship, positive correlation between education (p-value = 0.000), knowledge (p-value= 0.000), and facilities (p-value= 0.000) with family support and have moderate close relationship and also positive correlation between income (p-value= 0.000), motivation (p-value= 0.000), self-efficacy (p-value= 0.000), time availability (p-value= 0.000), and the attitude of health workers (p-value= 0.000) with family support and have strong close relationship. However, age variable (p-value= 0.111) shows no correlation. It can be concluded that there is a positive correlation between self-efficacy and family support with strongest close relationship (r = 0.649), it is hoped that health workers can provide counseling related to self-efficacy in Kelurahan Pondok Petir.